BRAF and NRAS locus-specific variants have different outcomes on survival to colorectal cancer - Summers, MG; Smith, CG; Maughan, TS; Kaplan, R; Escott-Price, V; Cheadle, JP (American Association for Cancer Research, 2016)
Purpose: Somatic mutation status at KRAS, BRAF, and NRAS is associated with prognosis in patients with advanced colorectal cancer (aCRC); however, it remains unclear whether there are intralocus, variant-specific differences in survival and other clinicopathologic parameters.Experimental Design: We profiled 2,157 aCRCs for somatic mutations in KRAS, BRAF, and NRAS and determined microsatellite instability status. We sought inter- and intralocus correlations between mutations and variant-specific associations with survival and clinicopathology.Results:KRAS mutations were rarely found together and those in codons 12 and 13 conferred poor prognosis [hazard ratio (HR), 1.44; 95% confidence interval (CI), 1.28-1.61; P = 6.4 × 10-10 and HR, 1.53; 95% CI, 1.26-1.86; P = 1.5 × 10-05, respectively]. For BRAF, more c.1781A>G (p.D594G) CRCs carried RAS mutations [14% (3/21)] compared with c.1799T>A (p.V600E) CRCs [1% (2/178), P = 9.0 × 10-03]. c.1799T>A (p.V600E) was associated with poor prognosis (HR, 2.60; 95% CI, 2.06-3.28; P = 1.0 × 10-15), whereas c.1781A>G (p.D594G) was not (HR, 1.30; 95% CI, 0.73-2.31; P = 0.37); this intralocus difference was significant (P = 0.04). More c.1799T>A (p.V600E) colorectal cancers were found in the right colon [47% (47/100)], compared with c.1781A>G (p.D594G) colorectal cancers [7% (1/15), P = 3.7 × 10-03]. For NRAS, 5% (3/60) of codon 61 mutant colorectal cancers had KRAS mutations compared with 44% (10/23) of codons 12 and 13 mutant colorectal cancers (P = 7.9 × 10-05). Codon 61 mutations conferred poor prognosis (HR, 1.47; 95% CI, 1.09-1.99; P = 0.01), whereas codons 12 and 13 mutations did not (HR, 1.29; 95% CI, 0.64-2.58; P = 0.48).Conclusions: Our data show considerable intralocus variation in the outcomes of mutations in BRAF and NRAS These data need to be considered in patient management and personalized cancer therapy. Clin Cancer Res; 23(11); 2742-9. ©2016 AACR.